(untitled) (Journal of Hama University, 2024)
This research aims to evaluate the safety and efficacy of tramadol in combination with half the effective dose of xylazine and ketamine used, and its effect on some clinical indicators and hematological parameters in dogs undergoing surgical castration. The research was conducted on 12 dogs (without progeny clinically healthy). with mean age (10±3.10) months and mean weight (12.5±1.93 kg), randomly divided among them into two groups, the first group (SXK) injected with 0,1 ml/kg of 0.9% NaCl solution and xylazine 2 mg/kg and ketamine 5.5 mg/kg intramuscularly, and the second group (TXK) injected tramadol 4 mg/kg and xylazine 1 mg/kg and ketamine 2.5 mg/kg intramuscularly. The surgical work lasted (10±1.48) minutes. All results were analyzed statistically at a significance level P≤ 0.05 .We found the time onset of anesthesia (3.83 ±0.41/ 4.83 ±0.41) minutes, anesthesia time (45±6.87 / 78±7.9) minutes, and the analgesia time (59.67±8.89/ 324±29.15) minutes in the first and second groups, respectively. The results of clinical indicators showed in the first group, a significant decrease in heart rate, respiratory rate and body temperature during the times (15-30-30-120) minutes postoperative, and a significant increase in the capillary refill time during the time (15-30-60-120) minutes postoperative. In the second group, a significant decrease in heart rate occurred during the periods (15-30-60) minutes postoperative, respiratory rate and body temperature during the times (15-30-60-120) minutes postoperative, and a significant increase in capillary refilling time during the times (15-30-60) minutes postoperative. The results of hematological parameters showed a significant decrease in the number of (RBC), (PLT), (Hb) and (PCV) in both groups during the periods (15-30-60-120) minutes postoperative, number of (WBC) showed no significant change in both groups. From the results, you can conclude that the TXK protocol is superior to SXK protocol in producing faster onset of anesthesia, longer duration of anesthesia and analgesia with lower doses, and lower effects on clinical indicators, while both protocols were equal in their effect on hematological parameters.